Implementasi Self Healing Pada Santri Pondok Pesantren Dan Peserta Didik Sekolah Negeri - Raihanah Raihanah (Lembaga Pengembangan Kinerja Dosen, 2022)
Mental health is very influential in the teaching and learning process, therefore it is important to maintain mental health so that the learning process runs effectively, one way to heal mental disorders such as emotional wounds is to do self-healing. This study discusses the comparison of the implementation of self-healing in Islamic boarding school students and students in public formal schools. By using a comparative research method with a qualitative approach and the data obtained through filling out a questionnaire (questionnaire) and interviews of 5 students and 5 students of state junior high schools. The results of the study show that there are differences in the implementation of self-healing in junior high school students and students based on where they are, the conditions and situations they are experiencing, students use self-healing more by drawing closer to Allah and putting their trust in God, while junior high school students are more able to do self-healing. Self-healing that students cannot do, such as using a mobile phone, is due to the rules that exist in Islamic boarding schools.